Pembangunan belia dari perspektif pengurusan Islam - Nik Abdullah, Nik Safiah
Youth is the largest group in the structures of society in our country. Thus, youth is our greatest and valuable asset for the country. Therefore, it is necessary for youths are brought up and guided to the right path and blessed by God so that they can be the generation that can be proud of the youth.This article discusses the youth development from an Islamic management perspective to produce individuals and subsequently the community of quality and personalized graceful.This article also applies the qualitative method through analysis of documents and data secondary sources. The outcome showed that the youth development from Islamic management perspective emphasizes the formation of high moral character and the skills based on Islam to achieve and meets the ideal brilliant youth.Hence, the youth as a great nation will appear when there is a comprehensive plan centered on four main elements, namely fertilization and supervision of the spiritual, physical, intellectual and emotional in line with Islamic teaching.Each field of Islamic teaching, whether in respect of tasawuf, aqidah or fiqh emphasizes the development of quality human equivalent.